PENGARUH PEMBELAJARAN ONLINE PADA MATA PELAJARAN SEJARAH TERHADAP MOTIVASI BELAJAR SISWA KELAS X SMK TARUNA PEKANBARU - Fariza, Chelsy Titivani; Isjoni, Isjoni; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of online learning on history subjects on the learning motivation of class X students of SMK Taruna Pekanbaru. The population in this study were all students of class X SMK cadets totaling 261 students and the sample in this study amounted to 100 students. Data collection techniques in this study using a questionnaire (questionnaire). The data analysis technique used is validity test, reliability test, simple linear regression test and coefficient of determination. The results showed that online learning had a positive effect on students' learning motivation.Key Word: online learning, motivation to learn